Listeria monocytogenes: An emerging food-borne pathogen and its public health implications - Reda, Waffa W; Abdel-Moein, Khaled; Hegazi, Ahmed; Mohamed, Yasmin; Abdel-Razik, Khaled (The Journal of Infection in Developing Countries, 2016)
Introduction: Listeria monocytogenes is considered one of the most important food-borne pathogens transmitted to humans via contaminated food. The aim of the present study was to demonstrate the importance of L. monocytogenes as a food-borne pathogen. Methodology: A total of 340 samples were collected from different localities in El Giza Governorate, Egypt, to check the occurrence of L. monocytogenes in that area. The collected samples comprised 250 food samples, 40 swabs from food refrigerators, and 50 stool specimens from diarrheic children. L. monocytogenes was isolated from the examined samples according to the International Organization for Standardization. The isolates were tested biochemically using Listeria Microbact 12L and confirmed by polymerase chain reaction. Results: The isolation rates of L. monocytogenes were 8% in beef burger, 4% in minced meat, 4% in luncheon meat, while sausage samples were all negative. Eight percent of raw milk samples were positive for L. monocytogenes, whereas cheese samples and refrigerator swabs were negative. Only Listeria grayi was isolated from human stools (2.5%). Conclusion: The high isolation rates of L. monocytogenes among the examined food stuffs highlight the crucial role of food as an important vehicle for this pathogen. More efforts should be made to ensure safe handling and processing of these foods to reduce the transmission of L. monocytogenes to humans.